A potential role for restricted intertactical heritability in preventing intralocus conflict. (28th September 2021) - Gamble, Madilyn M.; Calsbeek, Ryan G.
Abstract: Intralocus sexual conflict, which arises when the same trait has different fitness optima in males and females, reduces population growth rates. Recently, evolutionary biologists have recognized that intralocus conflict can occur between morphs or reproductive tactics within a sex and that intralocus tactical conflict might constrain tactical dimorphism and population growth rates just as intralocus sexual conflict constrains sexual dimorphism and population growth rates. However, research has only recently focused on sexual and tactical intralocus conflict simultaneously, and there is no formal theory connecting the two. We present a graphical model of how tactical and sexual conflict over the same trait could constrain both sexual and tactical dimorphisms. We then use Coho salmon ( Oncorhynchus kisutch ), an important species currently protected under the Endangered Species Act, to investigate the possibility of simultaneous sexual and tactical conflict. Larger Coho males gain access to females through fighting while smaller males are favored through sneaking tactics, and female reproductive success is positively correlated with length. We tested for antagonistic selection on length at maturity among sexes and tactics and then used parent–offspring regression to calculate sex‐ and tactic‐specific heritabilities to determine whether and where intralocus conflict exists. Selection on length varied in intensity and form among tactics and years. Length was heritable between dams and daughters ( h 2 ± 95% CI = 0.361 ± 0.252) and between fighter males and their fighter sons (0.867 ± 0.312), but no other heritabilities differed significantly from zero. The lack of intertactical heritabilities in this system, combined with similar selection on length among tactics, suggests the absence of intralocus conflict between sexes and among tactics, allowing for the evolution of sexual and tactical dimorphisms. Our results suggest that Coho salmon populations are unlikely to be constrained by intralocus conflict or artificial selection on male tactic.